2020
DOI: 10.29252/jpm.7.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice of Hormozgan province workers regarding the protection against COVID-19

Abstract: Introduction: Currently, the most important health priority of the whole world is COVID-19. Due to the lack of an effective treatment and vaccine for COVID-19, it is important to seriously focus of the prevention.The aim of this study was to investigate the Knowledge and practice of Hormozgan province workers regarding the protection against COVID-19. Methods: In this cross-sectional study, the study sample included 406 workers working in the Hormozgan province who were selected through an available sampling m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Therefore, these people performed COVID-19 preventive behaviors more frequently than other people. In line with this finding, Zare et al reported that the level of outdoor sports activity may be considered as one of the main predictors of performing behaviors effective on prevention of COVID-19 48 . Also, the finding of the present study was inconsistent with findings of a study by Ghiasvand and Taghizadeh.…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, these people performed COVID-19 preventive behaviors more frequently than other people. In line with this finding, Zare et al reported that the level of outdoor sports activity may be considered as one of the main predictors of performing behaviors effective on prevention of COVID-19 48 . Also, the finding of the present study was inconsistent with findings of a study by Ghiasvand and Taghizadeh.…”
Section: Discussionmentioning
confidence: 75%